The effects of allelochemicals from root exudates of Flaveria bidentis on two Bacillus species - Sun, Chaofang; Li, Qiao; Han, Lingling; Chen, Xue; Zhang, Fengjuan (Frontiers in Plant Science, 2022)
To determine the allelopathic effects of root exudates from Flaveria bidentis on function of Bacillus, pot experiment was used to collect root exudates from living plants and test its allelopathic effects on function of Bacillus frigoritolerans and Bacillus megaterium, which were two dominant bacteria in the rhizosphere soil of F. bidentis. To obtain the allelopathic substances, the root exudates were successively extracted by N-hexane, dichloromethane, ethyl acetate, and N-butanol, and their allelopathic effects were tested. The results showed that B. frigoritolerans and B. megaterium considerably increased the concentration of available phosphorus and nitrogen, respectively, when the soil was treated with different concentrations of root exudates. Among the four organic solvent extracts, dichloromethane extracts significantly increased the abundances of B. frigoritolerans and B. megaterium and promoted their nitrogen-fixing and phosphate-solubilizing abilities. Phenol was detected in dichloromethane extracts by gas chromatograph-mass spectrometer (GC-MS). Meanwhile, phenol promoted the ability to fix nitrogen of B. megaterium and its growth by increasing the soil available nitrogen concentration, but phenol promoted the ability to solubilize phosphate of B. frigoritolerans only in 0.1mg/mL concentration. Therefore, phenol was an allelochemicals in the root exudates of F. bidentis that affects the growth and activities of B. megaterium.